(untitled) (Fiep Bulletin - online, 2017)
Over the years man has managed to place himself in superiority over other animals, for an axiological reason,because we can distinguish between "good and evil." The composition of man in the matter of dualism proposed by variousphilosophers and influential cultures in previous years, Alma-Corpus, has achieved a differentiation of positions regarding theexplanation attributed by each author, some put their position against the domination and importance of the soul , And others inturn of the body.This is how it is emphasized that the human being is a composition, is a whole, composed of several fundamentalelements, which seeks the full realization of reason, is therefore proposed the relationship with Physical Education, as this Matteris not only limited corporal activity, it goes beyond, since it combines abilities, emotions, sensations and behaviors, making itmore complete and of greater value compared to the attributions that have been made to it currently.